REPLICATING STYLISTIC DEVICES IN TRANSLATION (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the critical role of stylistic devices in shaping the aesthetic and communicative impact of literary works and the intricate challenges translators face in rendering these devices effectively across languages. It explores various categories of stylistic devices, including figurative language, sound patterns, syntactic structures, and discourse features, illustrating the complexities involved in achieving equivalent stylistic effects in the target language. The article emphasizes that successful translation goes beyond mere lexical and grammatical transfer, requiring a deep understanding of both source and target language stylistic conventions and a creative approach to recreating their intended impact on the reader.